2021
DOI: 10.3389/fmed.2021.769740
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Statin Therapy on the Incidence of Cardiovascular Events, Cancer, and All-Cause Mortality in People Living With HIV: A Meta-Analysis

Abstract: Background: Possible influences of statin therapy on the risk of cardiovascular events, cancer, and all-cause mortality in people living with HIV (PLWH) remain unclear. We performed a meta-analysis to systematically evaluate the efficacy of statin in PLWH.Methods: Relevant cohort studies were retrieved via a search of the Medline, the Embase, and the Web of Science databases until June 14, 2021. The data were combined with a random-effects model by incorporating the between-study heterogeneity.Results: A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
(121 reference statements)
0
3
0
Order By: Relevance
“…Li and colleagues in a recent meta-analysis of 9 cohort studies involving 73, 256 participants found that statins were associated with a 44% reduction in all-cause mortality [40]. Additionally, another metaanalytic pooling of 7 cohort studies with 35,708 participants showed that statins decrease all-cause mortality by 33% in PLWH with/without HAART [41].…”
Section: Discussionmentioning
confidence: 99%
“…Li and colleagues in a recent meta-analysis of 9 cohort studies involving 73, 256 participants found that statins were associated with a 44% reduction in all-cause mortality [40]. Additionally, another metaanalytic pooling of 7 cohort studies with 35,708 participants showed that statins decrease all-cause mortality by 33% in PLWH with/without HAART [41].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the Johns Hopkins HIV clinical cohort that enrolled 1538 virally suppressed HIV individuals under statin treatment demonstrated a reduced risk of all-cause mortality after adjusting for CD4 count, HIV-1 RNA, hemoglobin, and cholesterol levels at the start of HAART, age, race, HIV risk group, prior use of ART, year of HAART start, NNRTI versus PI-based ART, prior AIDS-defining illness, and viral hepatitis coinfection [156]. The aforementioned data are strengthened by a recent meta-analysis of 36,253 HIV individuals undergoing statin treatment, where statin use was independently statistically correlated with a reduced mortality risk in PLWH [147].…”
Section: Statinsmentioning
confidence: 99%
“…Lipid disorders are more prevalent among HIV-infected patients whether they are taking ART medications or not. Understanding these dyslipidemias is important to screen or diagnose the cause of lipid disorder, which may lead to life-threatening cardiovascular diseases and will improve the treatment outcomes in HIV-infected patients, thus providing a better quality of life [14].…”
Section: Introductionmentioning
confidence: 99%